(untitled) (REMUNOM, 2023)
This study examined the effects of utilizing augmented reality (AR) technologies and educational booklets in the teaching of biochemistry to third-year high school students. With the aim of enhancing the teaching and learning process, a descriptive, observational, and experimental approach was employed, involving 37 students from CEFET/RJ. The digital resources employed included the booklet "Biochemistry in Everyday Life" and the "Biochemistry AR" application. The students’ progress was evaluated through a theoretical questionnaire and a self-assessment. The findings demonstrated that the utilization of these digital tools resulted in improved performance and comprehension of biochemistry concepts among the students, enabling them to visualize and apply abstract concepts in real-world scenarios. These outcomes indicate the potential for other educators to benefit from these findings and implement this promising methodology in their own classrooms. Keywords: Learning; Biochemistry; Digital resources;